(3Yjf GdEUGHI aj GSJOQGc YGFTI Ydi GdUMGHIs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hcai gPG LRA dNUJ ajg cJGH GdELGHI ajeG GSJOQcJg YGFTI Ydi GdUMGHI ddEeGe HOQ GdOjf GdRQcTj eY RjGOI eG JjSQ hbO SHb GdTjN HOQ GdOjf Edi GdJCdja aj Pdc GdCSJGoP CHh efUhQs
(3BNQgG (B:s
(3hCNQL GHf CHj TjHI Yf CHj gQjQI bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B" (3dG jeTjf GMOce aj fYd hGMOI hdG Na hGMO djfYdgeG LejYG Ch djeTjf ajgeG LejYG hCNQL Jes
(3Vef eLehY Hg QSGdI HNW eWGHb eDQNI (B1124 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3cTa GdXfhf (B2\1181s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdMOjK hGdeUWdMs